Sonic modernities in the Malay world : a history of popular music, social distinction and novel lifestyles (1930s-2000s) - Yampolsky, Philip, 1945- (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2014)
"Sonic Modernities situates Southeast Asian popular music in specific socio-historical settings, hoping that a focus on popular culture and history may shed light on how some people in a particular part of the world have been witnessing the emergence of all things modern. In its focus on pioneering artists, their creative use of new genres and border crossing technologies it aims at a rewriting of Southeast Asia's twentieth century from the perspective of popular music makers, the entertainment industry and its ever changing audiences"-- Provided by publisher.